2021
DOI: 10.1039/d1ra07440g
|View full text |Cite
|
Sign up to set email alerts
|

A top-down design for easy gram scale synthesis of melem nano rectangular prisms with improved surface area

Abstract: A novel practical method for the gram scale preparation of melem possessing a nano rectangular prism morphology and improved specific surface area through a top-down depolymerization design was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…64 The morphology and textural properties of the fabricated M/K hybrid were assessed by field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and N 2 adsorption/desorption isotherms in comparison with those of pristine Melem. 49 The SEM and TEM images (parts a and b of Figure 3, respectively) showed that Melem preserved its nanorectangular prism morphology (Figure S5) 49 after treatment with {Mo 72 Fe 30 }. A closer inspection of the images revealed some particles with an average size of 20−40 nm on the Melem's surface (sizes in red in Figure 3) almost with a uniform distribution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…64 The morphology and textural properties of the fabricated M/K hybrid were assessed by field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and N 2 adsorption/desorption isotherms in comparison with those of pristine Melem. 49 The SEM and TEM images (parts a and b of Figure 3, respectively) showed that Melem preserved its nanorectangular prism morphology (Figure S5) 49 after treatment with {Mo 72 Fe 30 }. A closer inspection of the images revealed some particles with an average size of 20−40 nm on the Melem's surface (sizes in red in Figure 3) almost with a uniform distribution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Upon excitation of the solid samples at 355 nm, an emission peak at 412 nm appeared for Melem. 49 Quenching of the PL intensity by 86% and a slight redshift (10 nm) after the incorporation of the Keplerate obviously show efficient separation of the carriers resulting from charge transfer between Melem and metal cluster, which is expected to increase the photochemical activity (Figure 2a). 64 As depicted in Figure 2b, considering the lower E HOMO , the level of Keplerate compared to Melem, electron transfer from Melem to the metal cluster seems feasible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One solution is to embed active single metal centers in 2D supramolecular structures, which allows control of their coordination and spatial assembly, e.g. via metal–nitrogen interactions. Such an approach has been explored as a means to stabilize single copper atoms forming highly active and selective sites to be employed as non-noble metal SACs in electrochemical reactions. Furthermore, nitrogen-rich organic materials have found importance as starting materials for scientific and industrial electrochemical applications. Among various 2D supramolecular compounds, nanostructured triazine derivatives have been extensively studied and discussed as promising low-cost, non-noble metal catalysts for sustainable energy conversion and storage systems. , Melamine (2,4,6-triamino-s-triazine, Figure a) is a commonly used building block for nitrogen-containing heterocycles. The deamination of melamine during thermal polymerization creates an intermediate product called melem (2,5,8-triamino-tri-s-triazine, 2,5,8-triamino-heptazine, Figure a), which also has been reported to form supramolecular assemblies capable of achieving a high electrocatalytic activity for the oxygen evolution reaction and oxidation reduction reaction (ORR) . , …”
Section: Introductionmentioning
confidence: 99%